2019
DOI: 10.3390/molecules24203715
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolaric Acid B Induces Growth Inhibition and Caspase-Dependent Apoptosis on Head and Neck Cancer Cell lines through Death Receptor 5

Abstract: Pseudolaric Acid B (PAB), diterpenoid isolated from the root bark of Pseudolarix kaempferi Gordon tree (Pinaceae), exhibits an anti-proliferative and apoptotic activity in various cancer cell lines but to date, the effects of PAB on head and neck cancer (HNC) cell lines remain to be elucidated. In this study, we showed that PAB significantly inhibited the viability and caspase-dependent apoptosis in HN22 cell line. PAB-induced apoptosis is through inducing death receptor 5 (DR5) together with the increase in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Previous evidence indicated that PAB-induced apoptosis in human cancer mainly associalted with the intrinsic mitochondrial pathway [7,13,17,31]. Choi et al recently reported that PAB could induce apoptosis in head and neck cancer cell lines through death receptor 5-mediated extrinsic pathway and increase the expression of cleaved caspase-8 [32]. In our study, we hypothesized that PAB induced apoptosis via intrinsic pathway in MG-63 cells.…”
Section: Discussionmentioning
confidence: 70%
“…Previous evidence indicated that PAB-induced apoptosis in human cancer mainly associalted with the intrinsic mitochondrial pathway [7,13,17,31]. Choi et al recently reported that PAB could induce apoptosis in head and neck cancer cell lines through death receptor 5-mediated extrinsic pathway and increase the expression of cleaved caspase-8 [32]. In our study, we hypothesized that PAB induced apoptosis via intrinsic pathway in MG-63 cells.…”
Section: Discussionmentioning
confidence: 70%
“…Guan et al 10 discovered that Hibiscus acid could effectively inhibit Wnt signal and PAX2 expression, increase Bcl-2-related X protein (Bax) expression level, and induce HeLa cell apoptosis. In addition, Choi et al 9 reported that Hibiscus acid promotes the apoptosis of hn22 cells by increasing the expression level of Caspase-8 and activating the exogenous apoptosis pathway mediated by death receptor 5 (DR5). In this study, we unveiled that PAB inhibited cell proliferation, invasion, and migration, but activated apoptosis of esophageal squamous carcinoma cell line TE-1.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Previous studies have also shown that PAB induces growth inhibition in different types of cancer via cell cycle arrest and apoptosis induction, such as ovarian cancer, lung cancer, prostate cancer, and leukemia. 9,10 PAB has considerable cytotoxicity against several cancer cell lines in the brain, colon, lung, breast, and kidney. 11,12 In the study of early pregnancy termination induced by artificial embryonic stem cells, researchers found that artificial embryonic stem cells may have anti-angiogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudolaric Acid B is a diterpenoid obtained from the root barks of Pseudolarix kaempferi Gordon tree. It has been noted to increase TRAIL-sensitivity (33). Intraperitoneal injections of ethanolic extracts of Pseudolarix kaempferi markedly reduced tumor growth in mice subcutaneously injected with HN22 cells (33).…”
Section: Natural Products Mediated Restoration Of Trail Pathwaymentioning
confidence: 99%
“…It has been noted to increase TRAIL-sensitivity (33). Intraperitoneal injections of ethanolic extracts of Pseudolarix kaempferi markedly reduced tumor growth in mice subcutaneously injected with HN22 cells (33).…”
Section: Natural Products Mediated Restoration Of Trail Pathwaymentioning
confidence: 99%